The Relationship between Social Media Use and Adolescents Perceptions and Attitudes About the Risk of Increasing HIV in SMAN 12 Makassar - Iismayanti Iismayanti; Sarina Sarina; Nurun Salaman (Pancasakti Journal Of Public Health Science And Research, 2025)
Adolescents' use of social media has become an integral part of their lives in the digital age. However, its uncontrolled use can bring negative impacts, including influencing risky sexual behavior. Social media allows adolescents to access adult content, potentially increasing promiscuous sexual behavior, the risk of developing sexually transmitted diseases, early marriage, pregnancy, and HIV. To determine whether adolescents' social media use, attitudes, and perceptions are associated with increased HIV risk. This study used a quantitative method with a cross-sectional descriptive study design using 189 students of class X SMAN 12 Makassar as the research sample. The results of the study based on the Fisher Exact alternative test obtained on perceptions with a p value of 0.125 and attitudes with a p value of 0.058 where the use of social media is in the positive category, perceptions and attitudes are in the positive category towards the risk of increasing HIV. There is no relationship between the use of social media with the perception of adolescents with an increased risk of HIV and there is no relationship between the use of social media with the attitude of adolescents with an increased risk of HIV.